Study on Meningitis Outbreaks due to Neisseria meningitidis in 2010 and 2012 in Burkina Faso - Savadogo, M.; Yelbeogo, D.; Zabsonre, S.; Tarbagdo, F.; Koussoube, D.; Ouedraogo, A. (Recent Developments in Medicine and Medical Research Vol. 1, 2021)
During the epidemic seasons in 2010 and 2012, epidemic outbreaks were recorded in several health districts in Burkina Faso. Climatic conditions, poverty and poor population immunity make it possible for the emergence of recurrent meningitis outbreaks by Neisseria meningitidis. Objective: Describing the epidemiology characteristics and response during epidemics of 2010 and 2012. Patients and Methods: It consisted in a descriptive cross-sectional study which was conducted during epidemics of 2010 and 2012. Data were collected in health districts. Meningitis cases are defined as suspect, probable or confirmed cases according to WHO definitions. The data were entered and analyzed using Epi Info 3 5 1. Outcomes: Twelve districts had crossed their epidemic threshold in 2010 and thirteen in 2012. The isolated bacteria were dominated by Neisseria meningitidis X in 2010 and Neisseria meningitidis W in 2012. The average age of patients was 12 years in 2010 and 9 years in 2012. The sex ratio was 1.3 in 2010 and 1.3 in 2012 in favor of the male. The modal age group was that of 5 and 14 years respectively in 2010 and 2012. Three health districts had a vaccine response with uncombined polysaccharide vaccine ACYW. The appropriate management of cases and children immunity strengthening remain major strategies against meningitis epidemics. It is important to acquire combined tetravalent ACYW vaccine for adapted vaccine response in case of epidemics.